Rumbling in High Speed Passenger Trains - Meywerk, M. (Engineering Transactions, 1998)
A model of a flexible wheel set running on flexible rails is presented. It gives hints for the reasons of rumbling in the high-speed passenger train InterCityExpress (ICE) of the German railway company (DB) if these trains travel on the new stiff tracks. The rumbling results from non-circular wheels which cause oscillations of the whole system. The problem of polygonization of railway wheels is not considered.